Changes in genetic evaluation of dairy cattle: the animal model - Heikes, K. (Kansas Agricultural Experiment Station, 2012)
The July 1989 USDA Sire Summary introduced a new system for genetic evaluations in dairy cattle. These evaluations, known as the Animal Model (AM), include several new features that help to increase the accuracy of evaluations compared to the way sire summaries were calculated in the past.
The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy; Genetics; Performance; Animal Model (AM)